Pelaksanaan Praktikum Mata Kuliah Fisika Dasar I pada Program Studi Pendidikan Fisika FKIP UNSAM Semester Ganjil Tahun Akademik 2017/2018 - Teuku Hasan Basri; Bachtiar Akob (Jurnal Pendidikan Fisika dan Sains, 2018)
Based on the Physics Education Study Program curriculum at the FKIP Samudra University, 1st Basic Physics course in the first semester of the lecture, where the course is 4 credits. The learning process, 3 credits of face-to-face process in the classroom, 1 credits carry out lab work in the laboratory. Problem formulation, "How far is the implementation of the 2017/2018 odd semester 1 Physics course practicum in the Physics study program FKIP Samudra University. The purpose of this study is," To find out the practicum of the Basic Physics course 1 odd semester 2017/2018 in physics studies FKIP Samudra University. The population of this study is, "All 2017/2018 odd semester students in the physics study program at the FKIP Samudra University, amounted to 23 people. Sampling was taken by total sampling, so the sample size was 23 people. The data collection method in this study used a questionnaire, which was divided into 23 students data processing methods, using simple statistics namely "percentage formula", namely: . onclusion, based on the results of research and data processing, the authors draw the following conclusions: 1. Basic Physics Practicum 1 semester 2017/2018 in the Physics study program FKIP Samudra University has been implemented, but is still limited to material: Calipers, scrop micrometers and waves . 2. There are basic physics practicum material 1 that have not been carried out in the 2017/2018 odd and fluid semester in optics, although equipment and facilities are available. Keywords: Practicum, Basic Physics 1, Students